2016
DOI: 10.1007/s00253-016-7667-5
|View full text |Cite
|
Sign up to set email alerts
|

Design of a covalently linked human interleukin-10 fusion protein and its secretory expression in Escherichia coli

Abstract: Wild-type human interleukin-10 (hIL-10) is a non-covalent homodimer with a short half-life, thus limiting its therapeutic applications in vivo. To avoid loss of function due to dimer dissociation, we designed a synthetic hIL-10 analog by bridging both monomers via a 15 amino acid-long peptide spacer in a C-terminal to N-terminal fashion. For secretory expression in Escherichia coli, a 1156 bp fragment was generated from template vector pAZ1 by fusion PCR encoding a T7 promoter region and the signal sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Enhancement of extracellular protein expression through glycosylation in P. pastoris had been reported for lipase and other proteins (Yang et al 2015a,b). Fusion protein expression is a common strategy to improve the expression or soluble expression of the target protein (Guggenbichler et al 2016). However, the fusion expression with an endogenous protease Kex2 failed to obtain high level of RML expression in GS-RMk-kTL in our study, compared with the fusion protein in GS-RMG-pTL, GS-RMG-TL, GS-RMD-pTL and GS-RMD-TL, which indicated that the expressed RML protein was extensively degraded during post-translational modification and secretory process.…”
Section: Fusion Expression Of Lipase Isozymesmentioning
confidence: 99%
“…Enhancement of extracellular protein expression through glycosylation in P. pastoris had been reported for lipase and other proteins (Yang et al 2015a,b). Fusion protein expression is a common strategy to improve the expression or soluble expression of the target protein (Guggenbichler et al 2016). However, the fusion expression with an endogenous protease Kex2 failed to obtain high level of RML expression in GS-RMk-kTL in our study, compared with the fusion protein in GS-RMG-pTL, GS-RMG-TL, GS-RMD-pTL and GS-RMD-TL, which indicated that the expressed RML protein was extensively degraded during post-translational modification and secretory process.…”
Section: Fusion Expression Of Lipase Isozymesmentioning
confidence: 99%